The Araras Escarpment in the upper Paraná River: implications to fluvial neotectonics on the Paraná drainage net evolution - Etchebehere, Mario Lincoln; Fulfaro, Vicente José; Saad, Antonio Roberto; J. Perinotto, José Alexandre (Revista Brasileira de Geomorfologia, 2005)
The Paraná River hydrographical basin, the second largest in South America, has in its upper reach an anomalousgeomorphological structure, in relation to the general NNE-WSW channel direction. This anomaly occurs southadjacent to the Rio do Peixe river mouth, where the Paraná River makes a U turn controlled by an unique antitheticfault block dipping W. This alteration occurs against the general pattern of the synthetic fault blocks dipping E of itsleft margin. This anomalous pattern is in accordance to the presence of a NW-SE shear megazone ruled by theGuapiara lineament. Geomorphological data and location of some clay deposits within this region indicate aprevious and more ancient channel for this river according with the general NNE-WSW direction of the TrêsLagoas Crustal Suture Zone. This new U pattern was formed only after the occurrence of a neotectonicreactivation at the crossing point among the Guapiara Lineament and the Três Lagoas Suture Zone. It is hereassumed that the lineament mode N350º appears as the most probable hydraulic tensor of this region and representsthe distensional direction. The lineament swarming N315º and N40º, as well as those grouped together in modeN115º, may favor transcurrent dextral movements for the NW quadrant and sinistral for the other two directionswith transtensive and transpressive deformation. Both are dependent on the local geometry of fracture plains andlocal stress fields. The most ancient geochronological data obtained until now for seismic liquefaction structuresamples from the Rio do Peixe valley, suggest a date of 34 ka BP, indicating that this tectonic regime was stillactive at this time.